Gastrostomy as a Preemptive Measure after Pancreatoduodenectomy against Delayed Gastric Emptying: A Small Case Series and a Review of the Literature - G. Floros; I. Galanis; P. Theodoropoulos; D. Bartziotas; C. Theodoropoulos; M. Metaxa; G. Giannos; P. Tsintavis; G. Stylianidis; S. Klimopoulos (Case Reports in Surgery)
Delayed gastric emptying (DGE) is a common (20–30%) postoperative complication following pancreatoduodenectomy (PD) (Parmar et al., 2013). Various causes and preemptive measures have been suggested to decrease the occurrence of DGE. We added a simple step in the procedure of 26 consecutive pancreatic head resections, which seems to alleviate DGE and has never been highlighted before.